DIGITAL MARKETING STRATEGIES FOR GREEN HEALTHY BEVERAGE DIVERSIFICATION: FROM INNOVATION AND ABSOPRTIVE CAPACITY PERSPECTIVE - Dewi Puspaningtyas Faeni; Herni Pujiati; Yohanes Ferry Cahaya (Bajang Institute, 2026)
This Community Service Program (PKM) was carried out to support the development of small and medium enterprises (SMEs) in healthy beverages, focusing on date milk products. The partner, Naning’s Catering in Ciputat Timur, South Tangerang, produces herbal drinks based on date milk, which have strong potential as functional foods due to their nutritional and health benefits. Despite increasing demand, the business faces challenges in semi-manual production, limited packaging design, and underutilization of digital marketing platforms, reducing competitiveness. The PKM team from Universitas Dirgantara Marsekal Suryadarma, together with students, provided solutions through three main activities: (1) improving production capacity with appropriate technology, (2) strengthening business management via training in analysis and marketing strategies, and (3) enhancing branding and digital promotion to expand market reach.